2011
DOI: 10.1002/aic.13711
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of PEI/PVP‐based carbon hollow fiber membranes for CO2/CH4 and CO2/N2 separation

Abstract: Carbon hollow fiber membranes derived from polymer blend of polyetherimide and polyvinylpyrrolidone (PVP) were extensively prepared through stabilization under air atmosphere followed by carbonization under N2 atmosphere. The effects of the PVP compositions on the thermal behavior, structure, and gas permeation properties were investigated thoroughly by means of differential scanning calorimetry, thermogravimetric analysis, X‐ray diffraction, and pure gas permeation apparatus. The experimental results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…It was found that the formed polymer chains had increased the packing density of the membranes, and some of the pores had become narrow due to the densification of carbon structure. Similar findings had also been reported elsewhere [16]. As the final carbonization temperature was increased, the gas passed through the membrane structure according to their kinetic diameter.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that the formed polymer chains had increased the packing density of the membranes, and some of the pores had become narrow due to the densification of carbon structure. Similar findings had also been reported elsewhere [16]. As the final carbonization temperature was increased, the gas passed through the membrane structure according to their kinetic diameter.…”
Section: Resultssupporting
confidence: 90%
“…This pattern is in agreement with the fact that at high temperature, carbonized membranes will possess a microporous structure that is capable to recognize different kinetic diameter of gases, which then will increase the selectivity. Similar findings were also reported by Salleh and Ismail [16]. The increasing trend suggested that the micropores formation and the carbon structure of the carbon membrane became rigid and compact; and some of the pores might change into closed pores during the carbonization process.…”
Section: Resultssupporting
confidence: 88%
“…Molecularly selective CMS membranes enable difficult gas separations and have good chemical, thermal, and mechanical properties . Such membranes are useful for natural gas, air, and petrochemical applications . Optimizing the permeability and selectivity of CMS membranes by tailoring precursors and/or optimizing pyrolysis conditions are accepted approaches .…”
Section: Figurementioning
confidence: 99%
“…[21] TheC MS pore morphology includes micropores (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) between the stacks of sheets and smaller ultramicropores (< 7 )within the individual sheets (Supporting Information, Figure S1). [21] TheC MS pore morphology includes micropores (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) between the stacks of sheets and smaller ultramicropores (< 7 )within the individual sheets (Supporting Information, Figure S1).…”
mentioning
confidence: 99%